PENGARUH MANAJEMEN KELAS DAN DISIPLIN BELAJAR TERHADAP MOTIVASI BELAJAR SISWA KELAS V DI SEKOLAH DASAR - Bahrun Alim; Farhan Saefudin Wahid; Robert Rizki Yono (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to analyze a) the effect of classroom management on the learning motivation of fifth grade students at SDN 01 Luwunggede. b) the influence of learning discipline on the learning motivation of fifth grade students at SDN 01 Luwunggede. c) the influence of class management and learning discipline on the learning motivation of fifth grade students at SDN 01 Luwunggede. This study uses a quantitative approach using explanatory research, namely research that aims to explain the relationship between two or more variables with the aim of obtaining valid data. The research data used are a) questionnaires in the form of written question data which are then distributed to respondents to be filled out. b) documentation in the form of pictures of the research process c) literature study containing literature references that support research. The data analysis technique used is with the help of the SPSS version 25 application. The results of this study show that classroom management has a positive effect of 17.20% on the learning motivation of fifth grade students at SDN 01 Luwunggede, Tanjung sub-district, learning discipline has a positive influence of 32.20% on the learning motivation of fifth grade students at SDN 01 Luwunggede Tanjung sub-district, class management and student learning discipline have a simultaneous positive influence of 42.90% on the learning motivation of fifth grade students at SDN 01 Luwunggede Tanjung sub-district.